Analysis Of Optimal Motion Performance For Underactuated Gantry Crane System Using MOPSO With Linear Weight Summation Approach - Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda; Ghazali, Rozaimi; Mohamed, Zaharuddin; Jamian, Jasrul Jamani; Mohd Aras, Mohd Shahrieel; Mohd Nasir, Mohamad Na'im; Sulaiman , Mohd Fairuz (IJET, 2014)
-